(untitled) (Eureka Journal of Language, Culture & Social Change, 2026)
Linguist it is known from the research of scientists that language units that are directly related to human life and daily activities are ancient, and they are distinguished by their stable nature and minimal exposure to various linguistic changes. The creation, regulation, and interpretation of linguistic expressions related to water are among the issues of attention. Issues such as the linguistic nature of units related to clean water, high-quality drinking water, used water, water treatment methods, wastewater, and the regulation and improvement of their presentation in dictionaries increase the need for linguistic study of field terms. This article analyzes the nominative, semantic, and etymological characteristics of lexical units expressing concepts related to wastewater, its formation, and treatment in the Uzbek language. In particular, folk and terminological naming models are comparatively highlighted based on units such as toshnov, tashnov, obrez, hanik, obbandon, obgoh, obbandi, obkhona, mag’zavakhona, kirora, and kanalizatsiya. The results of the study show the place of this lexicon at the junction of language and culture.